screening for cognitive impairment in late onset depression in a Brazilian sample using the BBRC-edu - Novaretti, Tânia Maria Da Silva [UNESP]; Radanovic, Marcia; Nitrini, Ricardo (Associação de Neurologia Cognitiva e do Comportamento, 2012)
Depression and dementia are the most prevalent neuropsychiatric disorders in the elderly population. Alzheimer's disease is the leading cause of dementia in most countries, being responsible for more than half of all dementia cases. Late-onset depression is a frequent cause of cognitive decline in the elderly. Differentiating between cognitive impairment secondary to depression and incipient dementia poses a challenge in the clinical setting.

Depressão e demência são os transtornos neuropsiquiátricos de maior prevalência na população idosa. A doença de Alzheimer é a principal causa de demência na maioria os países, sendo a responsável por mais da metade dos casos de demência. Depressão de início tardio é uma causa frequente de declínio cognitivo no idoso. A diferenciação entre transtorno cognitivo secundário à depressão e demência em fase inicial é um desafio na prática clínica.
RASTREIO DE COMPROMETIMENTO COGNITIVO NA DEPRESSÃO DE INÍCIO TARDIO EM UMA AMOSTRA BRASILEIRA USANDO O BBRC-EDU
Keywords: Alzheimer's disease; CERAD; BBRC-Edu; depression; screening test; cognition; elderly.; doença de Alzheimer; CERAD; BBRC-Edu; depressão; testes de rastreio; cognição; idosos.